High-temperature tribological properties of Co-29Cr-6Mo alloy fabricated by selective laser melting process - Ramezani, Maziar; Mohd Ripin, Zaidi (Frontiers in Mechanical Engineering, 2023)
This paper discusses the experimental procedure and results of an investigation into the sliding wear behavior of Co-Cr-Mo specimens produced by selective laser melting (SLM) process. The sliding wear tests were carried out with different normal loads, sliding frequencies, and temperatures. The results showed that the coefficient of friction decreased as the applied normal load increased due to the temperature effect. The wear rate increased significantly at higher loads due to increased surface stresses. Testing the specimens at elevated temperatures resulted in a decrease in COF due to thermal softening and the formation of an oxide layer on the surface. The wear rate increased for specimens tested at 200°C due to a decrease in hardness and strength, but the wear rate decreased at higher temperatures due to the protective effect of the oxide layer. The obtained results showed the SLM-printed Co-Cr-Mo alloy exhibited good mechanical properties and wear resistance, making it a promising material for tribological applications, especially at elevated temperatures.